Oxygen-plasma-modified biomimetic nanofibrous scaffolds for enhanced compatibility of cardiovascular implants - Pappa, Anna Maria; Karagkiozaki, Varvara; Krol, Silke; Kassavetis, Spyros; Konstantinou, Dimitris; Pitsalidis, Charalampos; Tzounis, Lazaros; Pliatsikas, Nikos; Logothetidis, Stergios (Beilstein Journal of Nanotechnology, 2015)
Electrospun nanofibrous scaffolds have been extensively used in several biomedical applications for tissue engineering due to their morphological resemblance to the extracellular matrix (ECM). Especially, there is a need for the cardiovascular implants to exhibit a nanostructured surface that mimics the native endothelium in order to promote endothelialization and to reduce the complications of thrombosis and implant failure. Thus, we herein fabricated poly-ε-caprolactone (PCL) electrospun nanofibrous scaffolds, to serve as coatings for cardiovascular implants and guide tissue regeneration. Oxygen plasma treatment was applied in order to modify the surface chemistry of the scaffold and its effect on cell attachment and growth was evaluated. The conditions of the surface modification were properly adjusted in order to define those conditions of the treatment that result in surfaces favorable for cell growth, while maintaining morphological integrity and mechanical behavior. Goniometry (contact angle measurements), scanning electron microscopy (SEM), atomic force microscopy (AFM), and X-ray photoelectron spectroscopy (XPS) measurements were used to evaluate the morphological and chemical changes induced by the plasma treatment. Moreover, depth-sensing nanoindentation was performed to study the resistance of the plasma-treated scaffolds to plastic deformation. Lastly, the cell studies indicated that all scaffolds were cytocompatible, with the plasma-treated ones expressing a more pronounced cell viability and adhesion. All the above findings demonstrate the great potential of these biomimetic tissue-engineering constructs as efficient coatings for enhanced compatibility of cardiovascular implants.
Keywords: cardiovascular implants; electrospun nanofibers; plasma treatment; scaffold; tissue engineering